2021
DOI: 10.1140/epjc/s10052-021-09076-x
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological inflation driven by a scalar torsion function

Abstract: A viable model for inflation driven by a torsion function in a Friedmann background is presented. The scalar spectral index in the interval $$0.92\lesssim n_{s}\lesssim 0.97$$ 0.92 ≲ n s ≲ 0.97 is obtained in order to satisfy the initial conditions for inflation. The post inflationary phase is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…Modified gravity theories with curvature-matter coupling [114][115][116] could also be extended to a Finslerian geometric framework. Riemannian geometries with torsion [117,118] or nonmetricity [119][120][121] can also represent a source of inspiration for obtaining their Finslerian analogues.…”
Section: A Metric and Thermodynamic Quantitiesmentioning
confidence: 99%
“…Modified gravity theories with curvature-matter coupling [114][115][116] could also be extended to a Finslerian geometric framework. Riemannian geometries with torsion [117,118] or nonmetricity [119][120][121] can also represent a source of inspiration for obtaining their Finslerian analogues.…”
Section: A Metric and Thermodynamic Quantitiesmentioning
confidence: 99%
“…respectively. 7 Our last step is to plug these results back into the Friedmann equations (see expressions (55a) and (55b) above) and in so doing arrive at…”
Section: Generalized Unconstrained Hyperfluidmentioning
confidence: 99%
“…Naturally, such fundamental modifications have a strong impact on the cosmic evolution and alter the Friedmann equations in a non-trivial manner [4]. For instance, in [5][6][7] and also in [8], it was shown that torsion can drastically alter the cosmological evolution and provide intriguing new results. From the geometrical point of view, torsion reflects the fact that the parallel transport of two vectors along each other does not form a closed parallelogram.…”
Section: Introductionmentioning
confidence: 99%
“…Different restrictions of non-Riemannian geometry provide distinct frameworks for gravity theories formulations and the inclusion of torsion and non-metricity in gravitational theories has led to many fruitful applications in various areas of both mathematics and physics, among which, for instance, the ones recently presented in [6][7][8][9][10][11][12][13][14][15]. In particular, in the cosmological context, in [15] the most general form of acceleration equation in the presence of torsion and non-metricity was derived and conditions under which torsion and non-metricity accelerate/decelerate the expansion rate of the Universe were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…These terms have exactly the same dimension as R, that is [L −2 ], and therefore their inclusion is well motivated 2. In[11] (see also[12][13][14], where the form of torsion presented in[11] was constrained), where only the Ricci scalar was present in the gravitational action, the conservation law for hypermomentum was trivialized leaving, therefore, the torsion function fully undetermined. It will be shown in the sequel that the very presence of the quadratic torsion terms fixes this indeterminacy, providing exact evolution laws for all variables.…”
mentioning
confidence: 99%